The performer is us. - Chadabe, Joel (Contemporary Music Review, 1999)
Interactive media present new opportunities for composers to create compositions that allow members of the public, even those without musical skill, to become performers. A categorization of different types of interactive realtime music is proposed from the perspective of the performer's role.